In silico and in vitro evaluation of primers for molecular differentiation of leishmania species - Trigo, Beatriz Batista [UNESP]; de Oliveira-Rovai, Fernanda Muller [UNESP]; Milanesi, Marco [UNESP]; Ito, Pier Kenji Rauschkolb Katsuda [UNESP]; Utsunomiya, Yuri Tani [UNESP]; Lopes, Flávia Lombardi [UNESP]; Paulan, Silvana de Cássia [UNESP]; Nunes, Cáris Maroni [UNESP] (FapUNIFESP (SciELO), 2021)
Leishmaniasis is a zoonotic disease caused by over 20 species of protozoan parasites of the genus Leishmania. Infection is commonly spread by sandflies and produces a wide spectrum of clinical signs and symptoms. Therefore, from an epidemiological and therapeutic standpoint, it is important to detect and differentiate Leishmania spp. The objective of this study was to combinate in silico and in vitro strategies to evaluate the analytical specificity of primers previously described in the literature. According to electronic PCR (e-PCR) analysis, 23 out of 141 pairs of primers selected through literature search matched their previously reported analytical specificity. In vitro evaluation of nine of these primer pairs by quantitative PCR (qPCR) confirmed the analytical specificity of five of them at the level of Leishmania spp., L. mexicana complex or Leishmania and Viannia subgenera. Based on these findings, the combination of e-PCR and qPCR is suggested to be a valuable approach to maximize the specificity of new primer pairs for the laboratory diagnosis of infections with Leishmania spp.
Avaliação in silico e in vitro de iniciadores para a diferenciação molecular de espécies de leishmania
Keywords: Differential diagnosis; E-PCR; Leishmaniasis; QPCR